“Actividades de musicoterapia para el desarrollo de la coordinación motriz en los niños de educación inicial” - Cola Ramos, Julenne Ivonne (2024)
The present research work refers to the use of music therapy as an innovative tool for strengthening motor skills in children, for this reason, the general objective has been the design of activities related to music therapy as a didactic strategy to support the development of motor coordination in children of Initial Education of the “Victoria Vásconez Cuvi” Educational Unit of the Latacunga city. For the design of this proposal, the constructivist pedagogical model has been taken as the central axis, being the one that prevails in the educational model of Ecuador. According to the analysis previously carried out, investigative methods and techniques have been used as the interview applied to teachers, obtaining as evidence the don’t use of innovative resources as music, which has not allowed children to continue strengthening motor coordination adequately. On the other hand, the don’t of innovative strategies in the teaching-learning process of students decreases the motivation to participate in each activity that is proposed. Due to the aforementioned, it is considered important and necessary to carry out dynamic elements in the educational process of children, which will be applied by teachers who will support the development of motor coordination and the use of music therapy as a pedagogical tool that will benefit the children's development.